The Effect Of Differentiated Learning On Academic Self-Confidence Of Fifth-Grade Students At Sd Negeri 20 - Fathona, Ukhtun; Beki Junianti; Wildan Murtadho; Pahrozi Ahmad (International journal of technology and education research, 2026)
This study aims to analyze the effect of differentiated learning on the academic self-confidence of fifth-grade students at SD Negeri 20, Bengkulu City. The background of this study is based on the low academic self-confidence of students, which is indicated by the lack of active participation in learning. This study uses a quantitative approach with a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of 48 students divided into an experimental group and a control group. Data were collected using an academic self-confidence questionnaire that had been tested for validity and reliability. Data analysis used descriptive statistics, normality tests, linearity tests, and hypothesis testing using independent sample t-tests. The results showed that the average academic self-confidence of students in the experimental group increased from 62.5 to 82.3 with a standard deviation of 6.5, while in the control group it increased from 63.1 to 70.2 with a standard deviation of 7.1. The results of the hypothesis test showed a significance value of 0.000 < 0.05, indicating a significant effect of differentiated learning on students' academic self-confidence. In addition, the coefficient of determination (R Square) value of 0.302 shows that differentiated learning contributes 30.2% to increasing students' academic self-confidence.